The dialogic-imaginative character of creativity and innovation in Adam Smith (Cultura Económica, 2021)
Adam Smith’s emphasis on the increase in productivity brought about by the division of labour in the Wealth of Nations led his general conception of the dynamics of economic growth to be associated almost exclusively with the productive specialization of labour and the free expansion of competitive markets. In this article we will try to show another perspective on Smithian economic growth. This perspective focuses on two fundamental aspects: on the one hand, the importance of imagination in creative-innovative processes, and, on the other, the dialogical basis of division of labour. In this way, we propose that an integral reading of Smith’s work is relevant, not only to reach a more complete understanding of the author’s own economic ideas, but also to provide interesting suggestions for thinking about the dynamics of growth and development today.
Keywords: ADAM SMITH; ECONOMIC GROWTH; CREATIVITY; INNOVATION; DIVISION OF LABOUR; IMAGINATION; LANGUAGE